BIOSYNTHESIS & CHARACTERIZATION OF STRONTIUM NANOPARTICLES FROM GRACILARIA CORTICATA SEAWEED AND THEIR ANTICOAGULANT PROPERTIES - B.L Ojastha, Dr. Abirami Arthanari (Chelonian Research Foundation, 2023)
INTRODUCTION: Gracilaria corticata, a red macroalgae commonly found in coastal regions, possesses bioactive compounds like phycoerythrin, hydrocolloids, polyphenols, and other compounds with exceptional medicinal properties. It is often found in marine environments, particularly in tropical and subtropical regions. Red algae like Gracilaria corticata play essential roles in marine ecosystems and can be used in various applications, including food products, cosmetics, and even as a source of agar, a gelatinous substance used in laboratories and the food industry.Seaweeds are also an excellent source of both soluble and insoluble dietary fiber. Among red algae, the genus Gracilaria contains a broad diversity of valuable contents for human nutrition and are one of the world’s most cultivated and valuable marine seaweed. Strontium nanoparticles (SrNPs), which are metallic nanoparticles, have drawn the most attention because of their unique physicochemical characteristics, which include chemical stability, biocompatibility, and low toxicity. Biogenic Strontium Nanoparticles are useful as antibacterial, antioxidant, and anticancer agents in the field of nanomedicine. Strontium Nanoparticles are also thought to be a viable and cutting-edge nutritional supplement for Sr. In this present study anticoagulant activity of Gracilaria Corticata mediated Strontium Nanoparticle is studied MATERIALS AND METHODS : An in vitro interventional study was conducted to study the anticoagulant activity of Gracilaria corticata mediated Strontium Nanoparticles. Aqueous extract of red algae that is Gracilaria corticata and Strontium nitrate solution is prepared. 50 ml of each of the solutions is taken. Kept in a Shaker for 60 hrs, and prepared the Strontium Nanoparticles. And tested for Nanoparticle characterization assay and anti coagulant assay. RESULTS: At the end of the experiment hatched embryos for hatching rate and viable embryos(delayed hatching) for viability rate were evaluated and analyzed statistically by one way ANOVA with SPSS software. CONCLUSION: This research confirms that the prepared Strontium Nanoparticles from Gracila Corticata possess potent anticoagulant properties through PTT and aPTT results and is safe to be used as therapeutic anticoagulant in various cardiovascular diseases to the conventional anticoagulant. KEYWORDS: Anticoagulant activity, Carrageenan, Gracilaria Corticata, Red algae,Strontium Nanoparticles, Sulfated Polysaccharide.